Mengenalkan Mitigasi Bencana dalam Praktik Kerja Lapangan di Lingkungan Kelurahan. - Harrys Cristian Vieri; Hairani Siregar (CV. KAMPUS AKADEMIK PUBLISING, 2023)
Field work practice or what is usually referred to as practicum is an activity held to practice the material that has been provided during teaching and learning activities. Fieldwork practice itself emerged with the existence of